Concentrations of Hormones During the Mid-Incubation Period in Kleptoparasitic and Honest Common Terns Sterna hirundo - Paterlini, Carla Ángela; García, Germán Oscar; Riechert, Juliane; Becker, Peter H (Acta Ornithologica)
Kleptoparasitism is a well-known foraging strategy used by many colonial seabirds. The expression of this behavior can reduce the cost of foraging during the breeding season and ultimately this can reflected in physiological parameters. Here we analyzed the relationship between the trophic strategy of Common Terns (Sterna hirundo) and two hormones: corticosterone (CORT) and prolactin (PRL). The study was conducted during the breeding seasons 2012-2014 at the Banter See colony in northern Germany where individuals with different foraging strategies were identified and monitored since 2008. We studied the concentration of hormones in two groups of birds: kleptoparasitic individuals (i.e. individuals who steal the food captured by another individual), and honest individuals (i.e. individuals who obtain the food on their own). Blood samples were obtained during the mid-incubation period using a non-invasive technique. Both hormones showed no significant relationship to each other. CORT concentration was similar in both groups of birds. However, the concentration of PRL was higher in parasitic than honest individuals in 2014. In addition, CORT modelling indicated a year effect (higher CORT in 2013), and PRL modelling indicated a significant effect of year (higher PRL in 2012) and a significant interaction between year and the trophic strategy in 2014. The results show no clear relationship between the feeding strategy and studied corticosterone and prolactin levels. Fil: Paterlini, Carla Ángela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: García, Germán Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del ...